Le développement des compétences interculturelles au moyen du jumelage international dans des universités française et canadienne - Lucie Le Callonnec
This study focuses on the mobility path of international students and, more specifically, a practice implemented by host universities to develop intercultural skills and facilitate integration into the local student community, namely international pairing. In this regard, two sets of interviews were conducted with nine international students, at the beginning and at the end of their mobility period. The sampling included five international students studying in Ottawa (Canada) and four in Montpellier (France). After students returned to their countries of origin, a questionnaire was also administered. Additional interviews were conducted with seven members of Canadian and French international offices. Our findings reveal that members of international offices, for the most part, strive to integrate international students by relying on the local student population through programs such as international pairing. However, despite interest shown by international students for this type of program, our results show that even if international students intend to initiate contact and establish relationships with the local community upon arrival in the host country, the reality is such that, often, at the end of their stay, students admit having few connexions with local students. Therefore, it is relevant to further explore integration and intercultural skills that international students developed during their mobility period and the role of pairing programs in this learning process.